Preparation of Sulfonated Polytriazoles with a Phosphaphenanthrene Unit via Click Polymerization: Fabrication of Membranes and Properties Thereof - Ghorai, Arijit; Roy, Sambit; Das, Sovik; Komber, Hartmut; Ghangrekar, Makarand M.; Voit, Brigitte; Banerjee, Susanta (ACS Applied Polymer Materials, 2021)
A phosphaphenanthrene-based diazide monomer, 1,1-bis-(4-azidophenyl)-1-(6-oxido-6H-dibenzc,e1,2oxaphosphorin-6-yl) ethane (DPAZ), was synthesized via diazonium compound formation. DPAZ was used as one of the comonomers along with a sulfonated diazide to prepare a series of sulfonated polytriazoles (PTDPBSH-XX, where XX denotes the molar percentage of the sulfonated diazide in the diazide mixtures) through copper-induced click polymerization with the bisphenol-based dialkyne (BPALK). The products were analyzed using Fourier transform infrared (FTIR) and NMR techniques. Size exclusion chromatography (SEC) results indicated the formation of high molar mass products (weight average molecular weight as high as 74900 g mol-1 with a polydispersity index (PDI) of 2.13). The polytriazoles showed high thermal stability, and the solution cast membranes from dimethyl sulfoxide (DMSO) were flexible and had good mechanical integrity. PTDPBSH-XX copolymers displayed high proton conductivity (141 and 152 mS cm-1 at 80 and 90 °C, respectively, for PTDPBSH-90 with a weight-based ion exchange capacity (IECW) of 2.46 mequiv g-1) with balanced water management and high oxidative stability (>16.5 h). The images of the cross-sectional membranes obtained from atomic force microscopy (AFM) and field emission scanning electron microscopy (FE-SEM) studies revealed hydrophilic-hydrophobic phase-segregated morphology. Besides, the microbial fuel cell performances of the membranes were comparable with that of Nafion 117.
CRIS-Team Scopus Importer:2022-04-14
Keywords: copolytriazole membranes; cyclic DOPO unit; microbial fuel cell; oxidative stability; proton conductivity